ANALISIS PERBANDINGAN PERKEMBANGAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) SEBELUM DAN SESUDAH MENDAPATKAN PEMBIAYAAN MIKRO MELALUI PROGRAM MEKAAR DI WILAYAH CAKUNG - Esti Damayanti, SE., M.Si.; Nur Amanah (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
Business capital is one of the things that is needed by micro, small and medium enterprises to develop a business. The purpose of this study is to analyze how the development of micro, small and medium enterprises before and after being given financing by financial institutions. The method used in this research is quantitative comparisons which are analyzed using the Paired Sample t-test analysis technique to test whether there is a difference in the mean of the two paired samples.